1991
DOI: 10.1038/bjc.1991.378
|View full text |Cite
|
Sign up to set email alerts
|

Glucose starvation and acidosis: effect on experimental metastatic potential, DNA content and MTX resistance of murine tumour cells

Abstract: Summary Exposure to oxygen deprivation in vitro has been reported to cause drug resistance in CHO cells (Rice et al., 1986; PNAS 83, 5978) and enhancement of experimental metastatic (colonisation) ability of murine tumour cells (Young et al., 1988; PNAS 85, 9533

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(98 citation statements)
references
References 45 publications
5
88
1
Order By: Relevance
“…Other factors, such as pH and low glucose may play a role (Schlappack et al, 1991). Also, hypoxia per se does not necessarily imply metastatic ability.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as pH and low glucose may play a role (Schlappack et al, 1991). Also, hypoxia per se does not necessarily imply metastatic ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown previously that exposure to acidic pH e in vitro may enhance the lung colonization potential of rodent tumor cells (27,28). In these experiments, KHT and B16 cells were exposed to pH e 6.5 for 48 hours and then allowed to recover at pH e 7.4 for 0, 24, or 48 hours before being inoculated i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent tumor cells exposed to acidic pH e in vitro were found to show enhanced lung colonization potential when inoculated i.v. in syngeneic host mice (27,28) whereas acidification of rodent tumors in vivo, obtained by administrating meta-iodo-benzylguanidine and/or glucose to the host mice, did not result in enhanced incidence of spontaneous lung metastases (29). Despite these conflicting observations, several studies have indicated that tumor cells exposed to acidic pH e in vitro may show increased expression of several genes known to promote invasive growth and metastasis, including genes encoding matrix degrading enzymes and proangiogenic factors (5,30).…”
Section: Introductionmentioning
confidence: 96%
“…However, cells in less extreme conditions of nutrient deprivation are likely to develop tolerance to the effect of PDT, due to GRP induction. These nutritionally deprived cells are known to have an increased metastatic potential (Schlappack et al, 1991), and may therefore serve as resistant foci for tumour progression. Unlike the problem of hypoxic inhibition of PDT (Mitchell et al, 1985;Wyld et al, 1998), there is a potential solution; infusions of glucose may elevate tumour glucose levels appreciably and therefore reduce the proportion of hypoglycaemic cells.…”
Section: Discussionmentioning
confidence: 99%